Drug resistant Mycobacterium tuberculosis in Mexico - Jorge Zazueta-Beltran; Claudia Leon-Sicairos; Adrian Canizalez-Roman (Journal of Infection in Developing Countries)
Tuberculosis (TB) remains a serious public health problem, worsened by an increased frequency of multidrug-resistant (MDR) Mycobacterium tuberculosis strains. The World Health Organization (WHO) and the International Union Against Tuberculosis and Lung Disease (IUATLD) launched the Global Project on Anti-Tuberculosis Drug Resistance Surveillance to measure the prevalence of drug resistance. Data from the global reports on resistance to anti-tuberculosis (anti-TB) drugs have shown that drug resistance still presents worldwide and that MDR-TB is present in almost all the world. Though the Global Project (WHO) has been operating since 1994, very few countries and states have reported new information. Data from repeated surveys employing comparable methodologies over several years are essential to determine with any certainty in which direction the prevalence of drug resistance is moving. Drug-resistant tuberculosis and MDR-TB have been identified in Mexico, even with the existence of a National Tuberculosis Program based on Directly Observed Treatment, Short-course (DOTS). This review discusses available surveillance data on drug susceptibility data for TB in different states of Mexico.